Evolutionary Genomics Provides Insights Into Endangerment and Conservation of a Wild Apple Tree Species, Malus sieversii - Jian Zhang; Fang‐Yuan Zhao; Hong‐Xiang Zhang (Evolutionary Applications)
ABSTRACT Understanding the evolutionary history of a species is essential for effective conservation management. Malus sieversii, a relict broad‐leaf forest tree found in arid Central Asian mountains, has a narrow and fragmented distribution and is classified as an endangered species in China. This species is considered one of the ancestors of the domesticated apple trees. In the present study, we sampled five populations of M. sieversii and its wide‐ranging congener M. baccata from China. Through deep whole‐genome resequencing, we analyzed the population's genetic diversity, genetic structure, demographic history, fixation of deleterious mutations, and genomic divergence. Our results revealed that M. baccata exhibits a higher level of genetic diversity than M. sieversii. The effective population size of M. sieversii decreased, whereas that of M. baccata recovered after the bottleneck effect. In M. sieversii, the genetic structure of the Yili region was distinct from that of the Tacheng region. Populations at the rear edge of the Tacheng region showed a stronger fixation of deleterious mutations than those in the Yili region. Genomic divergence indicated that the positively selected genes were associated with physiological processes within the genomic islands between the Yili and Tacheng regions. Based on these findings, we recommend the establishment of two separate conservation units for the Yili and Tacheng lineages to preserve their genetic resources. Given the limited distribution range and high fixation rate of deleterious mutations, urgent protective measures are recommended for the Tacheng lineage.